Adjustments for tax purposes in highly inflationary economies : proceedings of a seminar held in Buenos Aires in 1984 during the 38th Congress of the International Fiscal Association.: proceedings of a seminar held in Buenos Aires in 1984 during the 38th Congress of the International Fiscal Association. (2016) - Unknown
No abstract available